Energy, Exergy, and Economic Performance Analysis of Integrated CPVT with Supercritical CO2 Ejector Refrigeration Cycle for Residential Applications - H. Hawi Ogaili; S. Khalilarya; A. Chitsaz; P. Mojaver (Iranica Journal of Energy and Environment)
This study investigates the integration of a concentrated photovoltaic thermal (CPVT) module with a supercritical carbon dioxide (sCO₂) ejector refrigeration cycle to enhance sustainable cooling technologies. This research is significant as it explores the potential of sCO₂, a low-impact working fluid, in improving cooling efficiency within a novel energy system. The system’s performance was evaluated using calculations conducted in EES software, focusing on energy and exergy efficiencies, exergy destruction, and economic viability. The results revealed that the integrated system achieved notable energy and exergy efficiencies of 30.62% and 11.43%, respectively. Exergy destruction analysis identified the CPVT module and the boiler as the main sources of inefficiency, accounting for 77% and 14% of the total exergy destruction. Economic analysis highlighted the CPVT module as the primary investment cost driver. Sensitivity analysis demonstrated that increasing the solar panel area led to higher exergy destruction and costs without significantly improving efficiencies, while increasing the pump discharge pressure enhanced thermal efficiency but reduced exergy efficiency. These findings suggest that optimizing pressure levels within 6.5 to 11 MPa can lead to substantial variations in system performance, with thermal and exergy efficiencies varying by 82% and 18%, respectively. The novelty of this work lies in its comprehensive integration of CPVT and sCO₂ technologies, offering new insights into efficiency trade-offs and economic considerations for advanced cooling systems, thereby extending beyond previous literature efforts.